Discovery of a Selective Inhibitor for the YEATS Domains of ENL/AF9. (February 2019) - Christott, Thomas; Bennett, James; Coxon, Carmen; Monteiro, Octovia; Giroud, Charline; Beke, Viktor; Felce, Suet Ling; Gamble, Vicki; Gileadi, Carina; Poda, Gennady; Al-awar, Rima; Farnie, Gillian; et al.
Eleven-nineteen leukemia (ENL) contains an epigenetic reader domain (YEATS domain) that recognizes lysine acylation on histone 3 and facilitates transcription initiation and elongation through its interactions with the super elongation complex (SEC) and the histone methyl transferase DOT1L. Although it has been known for its role as a fusion protein in mixed lineage leukemia (MLL), overexpression of native ENL, and thus dysregulation of downstream genes in acute myeloid leukemia (AML), has recently been implicated as a driver of disease that is reliant on the epigenetic reader activity of the YEATS domain. We developed a peptide displacement assay (histone 3 tail with acylated lysine) and screened a small-molecule library totaling more than 24, 000 compounds for their propensity to disrupt the YEATS domain–histone peptide binding. Among these, we identified a first-in-class dual inhibitor of ENL ( K d = 745 ± 45 nM) and its paralog AF9 ( K d = 523 ± 53 nM) and performed "SAR by catalog" with the aim of starting the development of a chemical probe for ENL.